"GREEN" ENERGY: PROBLEMS OF DEVELOPMENT AND TARIFF FORMATION IN CONDITIONS OF UNCERTAINTY - FADYEYEVA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
A study of approaches to the development of renewable energy sources (RES) in economically developed countries of the world and in Ukraine was conducted with the aim of identifying the most effective and acceptable tools for stimulating the development of "green" energy as an alternative to traditional energy sources in the post-war period. The problems of the development of the use of renewable energy sources are of particular importance, as they are related not only to the energy sphere, but also to environmental problems, global climate changes, etc. Ukraine, as a member of the world community, cannot stand aside from theese problems even in the difficult and uncertain conditions of the ongoing war. On the basis of a systemic approach, the prospects for the further development of renewable energy sources (RES) are considered, as well as the main problems for the state economy related to tariff formation in "green" energy. The conducted research showed that there are practically no alternatives to the development of RES in Ukraine during the post-war recovery period, therefore the state should already review and improve the strategy of recovery and development of the economy, taking into account that RES will become the main source of energy in the coming decade. At the same time, the state must take the place of a key player in this market, show by its own example the expediency and effectiveness of investments in RES and create a favorable investment climate in this area by all possible means, in particular, high-quality tariff formation, to ensure the population’s access to clean energy and the timely fulfillment of climate obligations and restoration and development of the country’s economy. ays to solve this problem are proposed, based on the foreign experience of stimulating tariff formation and approaches to state investments in the field of RES.